Consideration on the Telecom Operators Developing Vehicle Network - Shuhui Ma; Yaliang Song; Bingyi Fang (Dianxin kexue)
As a representative of the third generation vehicle communication technology and a typica1 application of internet of things，vehicle network is being paid much attention to by the industry chain. The cha11enges were analyzed which vehicle network development is facing from the points of view of technology，market and business mode1 based on current status of application and research，and then the roles and opportunities of telecommunication operator in the industry chain were presented thoroughly. Fina11y，studies on the new technologies such as LTE，mobile internet and cloud computing which would impact on the future vehicle network.